PENERAPAN MODEL PEMBELAJARAN DISCOVERY UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI ENERGI BUNYI - Jayadinata, Asep Kurnia; Aeni, Ani Nur; Nur'aeni, Ratu Syafira (Jurnal Pena Ilmiah, 2017)
Based on observation taken on learning natural science subject ofÂ sound energy in class IV SDN Sindang II the outcome ofÂ learning of most student does not exceed Minimum Accomplishment Criteria. Due to the problem, this research is conducted by applying discovery learning model on science subject of sound energy. The objective of the research is to determine development of learning planning, performance of teacher, student activity, and outcome of student learn. The research uses class action research method that applying spiral model of Kemmis and Taggart that consists of the stage of planning, actuating, observation and reflection. This research shows on every phase planning of learning, teacher performance, student activity and student learning outcome was increased. Therefore, that application of Discovery Learning Model on learning of sound energy subject enhance outcome of student learn.